KENDALA FASILITAS SEKOLAH DALAM PROSES PEMBELAJARAN DAN TANTANGAN KURANGNYA KEDISIPLINAN GURU DI MADRASAH ALIYAH DARUL HUDA PUSAT MANDALAWANGI PANDEGLANG - M Sudi, Didih; Heni, Heni; Ernawati, Euis (Ta'dibiya, 2023)
This research took place at Madrasah Aliyah Darul Huda, Mandalawangi Center, regarding facilities constraints in the learning process, as well as the challenges of lack of discipline between teachers and students. This research aims to find out how the discipline exists at Madrasah Aliyah Darul Huda, Mandalawangi Center, and find out all the facilities that support the learning process. This research uses qualitative methods, and the results found from this research are; there is still a lack of discipline between teachers and students, as well as a lack of facilities that support the learning process. The future solution to this problem is to be able to improve discipline in the school again, and also to be able to complete the facilities for the learning process at the school.